2012
DOI: 10.1155/2012/291541
|View full text |Cite
|
Sign up to set email alerts
|

Earthing: Health Implications of Reconnecting the Human Body to the Earth's Surface Electrons

Abstract: Environmental medicine generally addresses environmental factors with a negative impact on human health. However, emerging scientific research has revealed a surprisingly positive and overlooked environmental factor on health: direct physical contact with the vast supply of electrons on the surface of the Earth. Modern lifestyle separates humans from such contact. The research suggests that this disconnect may be a major contributor to physiological dysfunction and unwellness. Reconnection with the Earth's ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 21 publications
0
35
0
1
Order By: Relevance
“…Following this, research in this academic field has grown exponentially and encompasses a large literature base on nature’s health benefits. These include improvements in neurological and circadian rhythms relating to exposures to natural sunlight (100, 101), undergoing “Earthing” or physical contact with the Earth’s surface regulates diurnal body rhythms (102) as well as walking activities in forest environments reducing blood pressure levels (8). …”
Section: Current Knowledge On the Human–nature Relationship And Healthmentioning
confidence: 99%
“…Following this, research in this academic field has grown exponentially and encompasses a large literature base on nature’s health benefits. These include improvements in neurological and circadian rhythms relating to exposures to natural sunlight (100, 101), undergoing “Earthing” or physical contact with the Earth’s surface regulates diurnal body rhythms (102) as well as walking activities in forest environments reducing blood pressure levels (8). …”
Section: Current Knowledge On the Human–nature Relationship And Healthmentioning
confidence: 99%
“…Hydrogen-rich water has a negative ORP value that can provide electricity to the body and lower the body's electrical potential similar to the action of grounding [4]. Molecular hydrogen is known to be the smallest molecule that can rapidly penetrate biomembranes into cells and displays antioxidant and anti-inflammation activities [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogen-rich water bath may provide electricity to the body and lower the body's electric potential similar to the action of grounding. Grounding is known to reduce the alternating current electric potential at the surface of the body and lower perturbations in electric charges of molecules inside the body [4]. Grounding can normalize the function of all body systems and improve sleep, relieve chronic pain, increase the respiratory rate and blood oxygenation, and reduce blood glucose, red blood cell aggregation, and inflammation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This property of air is known as the vertical potential gradient (VPG) of the global electric circuit (GEC) [36]. Studies have found that equalizing the electric potential between the surface and Earth and the human body (earthing) improves inflammatory markers [37, 38] and blood viscosity [39, 40]. Inflammation and blood viscosity are important factors in the pathogenesis of atherosclerosis and atherothrombosis [41, 42] and hypertension [43, 44], respectively.…”
Section: Discussionmentioning
confidence: 99%